Role of Microthrombus Formation in the Development of Ischemia/Reperfusion-induced Liver Injury in Rats - Okajima, Kenji; Harada, Naoaki; Kushimoto, Shigeki; Uchiba, Mitsuhiro (Thrombosis and Haemostasis, 2002)
Although tumor necrosis factor-α (TNF-α) has been shown to play a critical role in the pathologic process leading to ischemia/reperfusion (I/R)-induced liver injury in rats by activating neutrophils, it is not clear whether or not microthrombus formation induced by TNF-α contributes to the liver injury. In the present study, we investigated the role of microthrombus formation in I/R-induced liver injury in rats. Hepatic tissue levels of TNF-α were significantly increased after reperfusion, and these were higher in animals subjected to 120 min-hepatic I/R than in those subjected to 60 min-hepatic I/R. Fibrin deposition was observed histologically in the hepatic sinusoidal space only in animals subjected to 120 min-hepatic I/R. Both the decrease in hepatic tissue blood flow and the extent of liver injury in animals subjected to 60 minand 120 min-hepatic I/R were significantly inhibited by pretreatment with anti-rat TNF-α antibody. Although neutrophil elastase inhibitors inhibited the decrease in hepatic tissue blood flow and reduced liver injury in animals subjected to 60 min-hepatic I/R, anticoagulants did not show any effects. Both anticoagulants and neutrophil elastase inhibitors inhibited the decrease in hepatic tissue blood flow and reduced liver injury in animals subjected to 120 min-hepatic I/R. Therapeutic effects of anti-rat TNF-α antibody on the120 min-I/R-induced liver injury were more marked than those of each anticoagulant or each neutrophil elastase inhibitor, and were comparable to those of combined use of anticoagulants and neutrophil elastase inhibitors. These observations strongly suggest that TNF-α induces I/R-induced liver injury primarily by activating neutrophils, and it exacerbates liver injury by inducing microthrombus formation when the production of TNF-α is further increased.
Keywords: Ischemia/reperfusion-induced liver injury; tumor necrosis factor-α; microthrombus; neutrophil elastase; endothelial cell injury